Simulating Competing Customer Relationship Management (CRM) Models: A PLS-SEM Approach To Identifying The Best-Fit Model For Alumni Contribution in Higher Education - Shalihati, Fithriyyah; Sumarwan, Ujang; Hartoyo, Hartoyo; Yuliati, Lilik Noor (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: Higher education institutions (HEIs) are increasingly expected to maintain meaningful long-term relationships with alumni. Customer Relationship Management (CRM), particularly when integrated with social media, has emerged as a key strategy for fostering alumni engagement, satisfaction, and contribution.Purpose: This study aims to identify the best-fit structural model that explains alumni contributions through CRM and social media interaction, while also investigating the role of social media as a moderator, mediator, or intervening variable in these relationships.Design/methodology/approach: The study employed Partial Least Squares–Structural Equation Modeling (PLS-SEM) to simulate twelve alternative models using data from 271 alumni of IPB University. These models varied in CRM structure, the inclusion of satisfaction, and the positioning of social media within the pathway.Findings/Result: Twelve structural CRM models were simulated to examine the effect of CRM and social media on alumni outcomes. Among them, Model 12 demonstrated the best fit, with strong explanatory power (R²), predictive relevance (Q²), and low prediction error (RMSE/MAE). The model reveals a sequential pathway: CRM → Customer Satisfaction → Customer Engagement → Customer Loyalty → Alumni Contributions. CRM also influences Social Media, which in turn enhances Satisfaction. All structural paths are statistically significant, indicating that both CRM and social media play a critical role in driving alumni contributions through a satisfaction-based relational process.Conclusion: CRM in higher education is most effective when treated as a socially constructed process mediated by digital interaction. Social media strengthens institutional trust and emotional connection, playing a critical role in converting alumni satisfaction into sustained loyalty and contribution. Universities should implement social CRM strategies by leveraging digital platforms, personalizing alumni communication, and supporting long-term engagement programs.Originality/value: This study contributes to CRM theory by applying social construction theory to alumni engagement and offering an empirically validated model of how social media enhances relational CRM in HEIs. The findings have practical implications for alumni management strategies in the digital era. Keywords: CRM, social media, alumni engagement, higher education, social construction theory